PERANCANGAN DAN PELATIHAN APLIKASI SISTEM AKADEMIK SMK NEGERI 2 PURWODADI (SIKUAD) - Assiva, Mochamad Amry; Tanuji, Hadi; Ajipangestu, Drajad Bima (Fokus ABDIMAS, 2024)
This community service journal focuses on the design and training of an academic system application (SIKUAD) at SMK Negeri 2 Purwodadi. The project aimed to develop an efficient system for managing academic data and to provide comprehensive training for its users. The research employed action research methodology, involving needs analysis, system design, application development, testing, training, and evaluation phases. Results indicated successful application development tailored to user needs, enhanced data management efficiency, and improved IT skills among school stakeholders. Training sessions were effective in equipping users with necessary skills, leading to positive feedback and enhanced academic data management practices.The website is now accessible at sikuad.smkn2purwodadi.sch.id